Flight to liquidity and the Great Recession - Radde, Sören (Journal of Banking & Finance, 2015)
This paper argues that counter-cyclical liquidity hoarding by financial intermediaries may strongly amplify business cycles. It develops a dynamic stochastic general equilibrium model in which banks operate subject to agency problems and funding liquidity risk in their intermediation activity. Importantly, the amount of liquidity reserves held in the financial sector is determined endogenously: Balance sheet constraints force banks to trade off insurance against funding outflows with loan scale. A financial crisis, simulated as an abrupt decline in the collateral value of bank assets, triggers a flight to liquidity, which strongly amplifies the initial shock and induces credit crunch dynamics sharing key features with the Great Recession. The paper thus develops a new balance sheet channel of shock transmission that works through the composition of banks’ asset portfolios.